Sacred records in the landscape: the mirila of the Dalmatian hinterland. (16th November 2016) - Mirošević, Lena; Katić, Mario; Faričić, Josip
Abstract: This paper discusses former burial rites which resulted in memorials known as mirila . It deals with the custom of marking a temporary resting-place while transporting a deceased person, which was prevalent in the north-eastern Adriatic hinterland, manifested in the erection of mortarless stone structures, the remains of which can still be found in the landscape. The paper considers the material and symbolic components of the cultural landscape through the phenomenon of mirila in the central parts of the Croatian Adriatic hinterland: Ravni Kotari and Bukovica. At the same time, given the complexity of natural and socio-political factors, an attempt is made to establish how the custom arose in the spatial and historical context of the region.